2023
DOI: 10.3390/life13112176
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Scleroderma-Related Microstomia Using Hyaluronic Acid: An Interventional Study

Ofir Shir-az,
Ariel Berl,
Din Mann
et al.

Abstract: Systemic sclerosis (SSc) or scleroderma is a rare, systemic, autoimmune connective tissue disease. It causes increased collagen synthesis, leading to multi-organ sclerosis, including the skin and joints. Patients’ overall health and quality of life are harmed dramatically. Involvement of the face and, especially, the oral opening can limit patients’ ability to speak and eat, oral hygiene, and cosmetic appearance. Profhilo® (NAHYCO®) is an over-the-counter product consisting of pure hyaluronic acid. It is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In this regard, HCCs have already proved their efficacy to restore damaged skin or connective tissues in several applications. A recently published paper interestingly demonstrated the efficacy of HCCs to induce an amelioration in terms of skin quality, skin elasticity, and quality of life in patients affected by scleroderma when perioral injections have been performed [ 73 ]. Moreover, several studies also demonstrated the efficacy of HCCs to repair damaged skin in psoriasis [ 74 ] or acne scars [ 75 , 76 , 77 ] demonstrating the pivotal role of HCCs in regenerative medicine.…”
Section: Role In Regenerative Medicinementioning
confidence: 99%
“…In this regard, HCCs have already proved their efficacy to restore damaged skin or connective tissues in several applications. A recently published paper interestingly demonstrated the efficacy of HCCs to induce an amelioration in terms of skin quality, skin elasticity, and quality of life in patients affected by scleroderma when perioral injections have been performed [ 73 ]. Moreover, several studies also demonstrated the efficacy of HCCs to repair damaged skin in psoriasis [ 74 ] or acne scars [ 75 , 76 , 77 ] demonstrating the pivotal role of HCCs in regenerative medicine.…”
Section: Role In Regenerative Medicinementioning
confidence: 99%